FBI : Whiplash - Book 14 - Coulter, Catherine (New York : G.P. Putnams Sons : Jove Books, 2010)
Married FBI agents Lacey Sherlock and Dillon Savich are investigating a rather unusual case: Senator David Hoffman is experiencing a ghostly apparition with possible malicious intent. Theyre no closer to cracking the case when a call comes in from Connecticut: A top foreign Schiffer Hartwin employee has been found murdered behind the drug companys U.S. headquarters.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Murder -- Investigation; Fiction; Apparitions -- Fiction; Pharmaceutical industry -- Corrupt practices; Fiction; Maryland -- Fiction; Connecticut -- Fiction; Thrillers (Fiction)